Nineteenth-century music - Samson, Jim (Cambridge Cambridge University Press, 2002)
This comprehensive overview of music in the nineteenth century draws on the most recent scholarship in the field. It avoids mere repertory surveys, focusing instead on issues which illuminate the subject in novel and interesting ways. The book is divided into two parts (1800-1850 and 1850-1900), each of which approaches the major repertory of the period by way of essays investigating the intellectual and socio-political history of the time.